Xây dựng và phát triển văn hóa nhà trường tại cơ sở giáo dục phổ thông tỉnh Bình Dương - Trần, Thị Tuyết Mai (Tạp chí Giáo dục, 2024)
School culture has a great influence on the quality of life and the effectiveness of school operations. In the context of current general education innovation, it is required to build and develop school culture; focus on creating a green, clean, beautiful, friendly and safe working environment; promote the positivity, proactiveness, creativity and consensus of school members. Research shows that school culture in general education institutions has been paid attention to but is still limited. The article presents the results of a survey and analysis of the current state of school culture in some general education institutions in Binh Duong province. From there, it proposes measures to build and develop school culture, contributing to building a positive educational environment, creating a unique identity for each educational institution, meeting the requirements of current educational innovation. Each school, based on the regional characteristics, local socio-economic conditions and the actual situation of the school, creatively applies measures and methods of impact in building, nurturing, cultivating and developing a positive and healthy school culture.